Perlindungan Hukum Para Pihak Apabila Terjadi Wanprestasi Lelang Non Eksekusi Sukarela Secara Online Tanpa Pejabat Lelang - Dewi Anita; Herlin Nurdiani; Tasya Dania; Umi Maskanah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
As explained, auctions basically adopt the characteristics of a sale and purchase agreement (1457 BW), where the elements of price and goods are important elements. The difference is that auctions require the presence of an Auction Officer, especially for execution auctions and mandatory non-execution auctions. Auctions have special regulations (Lex Specialis), namely Vendu Reglement and Vendu Instructie as auction regulations which are still valid today. Apart from that, the implementation of auctions is also regulated in PMK 213/PMK.06/2020 concerning Instructions for Implementing Auctions. Online auctions are carried out through the e-Marketplace Auction Platform where the implementation is usually carried out without an auction official, for example auctions on eBay. The purpose of this research is to determine protection for parties who experience losses due to default. This research is legal research with a statutory approach, conceptual approach and case approach. The research results obtained are that the validity of online voluntary non-execution auctions without the presence of an auction official is valid by adopting the characteristics of a sale and purchase agreement. And the protection for the parties is the legal protection of the parties in the event of default in a non-execution auction, there are 2 (two) namely regulated in the ITE law regarding electronic transactions and Consumer Protection which explains the existence of compensation, as well as by taking legal action to resolve disputes, where the parties can choose resolution either through court, arbitration or other alternative dispute resolution institutions (conventional/online dispute resolution) in accordance with the provisions of the Laws and Regulations as the default is related to responsibility.